Multiphoton microscopy of live tissues with ultraviolet autofluorescence - Li, Chunqiang; Runnels, Judith M.; Pitsillides, Costas (My University, 2010)
Current research on multiphoton autofluorescence microscopy is primarily focused on imaging the signal from reduced nicotinamide adenine dinucleatide (NADH) in tissue. NADH levels in cells are useful reporters of metabolic information, as well as early indicators in precancer and cancer diagnosis. While NADH is typically imaged in the 400-500 nm spectral window, the amino acid tryptophan is the major source of tissue fluorescence in the Ultraviolet range. Here, we briefly review current progress in multiphoton autofluorescence imaging of live tissues and cells, and report our recent findings of in vivo mouse skin imaging based on multiphoton excited tryptophan autofluorescence. This new method enables noninvasive imaging of skin tissue at video-rate and allows for the visualization and identification of cellular components in the epidermis, dermis, and muscle layers. It is also possible to image through small blood vessels in the mouse skin and observe circulating leukocytes in situ
Keywords: In vivo imaging; Multiphoton-excited fluorescence microscopy (MPM); Tryptophan autofluorescence; Video-rate imaging